Covid-19-Associated Mucormycosis: Histopathology of the Deadly Fungal Infection - Nidhi Anand; Pallavi Srivastava; Ashish Chandra Agrawal; Nikhil Gupta; Anupam Das; Nuzhat Husain (International Archives of Otorhinolaryngology, 2024)
Introduction Many patients suffered from rhino-orbital-cerebral mucormycosis during the coronavirus disease 2019 (COVID-19) pandemic in India. Diabetes is a known risk factor of COVID-19 infection and mucormycosis.